2014
DOI: 10.1099/ijs.0.055319-0
|View full text |Cite
|
Sign up to set email alerts
|

Pontibacter indicus sp. nov., isolated from hexachlorocyclohexane-contaminated soil

Abstract: An orange-pigmented bacterial strain, designated LP100T, was isolated from hexachlorocyclohexane-contaminated soil (Lucknow, India). A neighbour-joining tree based on 16S rRNA gene sequences showed that strain LP100T occupied a distinct phylogenetic position in the Pontibacter species cluster, showing highest similarity with Pontibacter lucknowensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Starch, gelatin and chitin are not hydrolysed, while casein is hydrolysed. (Zhou et al, 2007); 9, P. niistensis NII-0909 T (Dastager et al, 2010); 10, P. ramchanderi LP43 T (Singh et al, 2013b); 11, Pontibacter xinjiangensis 311-10 T (Wang et al, 2010); 12, Pontibacter saemangeumensis GCM0142 T (Kang et al, 2013); 13, Pontibacter toksunensis ZLD-7 T (Zhang et al, 2013); 14, Pontibacter indicus LP100 T (Singh et al, 2013a). Phosphatydylethanolamine is the major polar lipid of all strains; all strains are positive for catalase; all strains are negative for denitrification activity.…”
Section: Description Of Pontibacter Ruber Sp Novmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch, gelatin and chitin are not hydrolysed, while casein is hydrolysed. (Zhou et al, 2007); 9, P. niistensis NII-0909 T (Dastager et al, 2010); 10, P. ramchanderi LP43 T (Singh et al, 2013b); 11, Pontibacter xinjiangensis 311-10 T (Wang et al, 2010); 12, Pontibacter saemangeumensis GCM0142 T (Kang et al, 2013); 13, Pontibacter toksunensis ZLD-7 T (Zhang et al, 2013); 14, Pontibacter indicus LP100 T (Singh et al, 2013a). Phosphatydylethanolamine is the major polar lipid of all strains; all strains are positive for catalase; all strains are negative for denitrification activity.…”
Section: Description Of Pontibacter Ruber Sp Novmentioning
confidence: 99%
“…At the time of writing, 13 species with validly published names had been described, with members of the species commonly isolated from habitats such as solar salterns, hexachlorocyclohexane (HCH) dump sites, rhizospheric soils, desert soils and sea water (Subhash et al, 2013b;Dwivedi et al, 2013;Xu et al, 2012;Raichand et al, 2011;Zhou et al, 2007;Nedashkovskaya et al, 2005;Kang et al, 2013). Five species were originally isolated in India, including: Pontibacter niistensis NII-0909 T (Dastager et al, 2010), Pontibacter lucknowensis DM9 T (Dwivedi et al, 2013), Pontibacter odishensis JC130 T (Subhash et al, 2013b), Pontibacter ramchanderi LP43 T (Singh et al, 2013b) and Pontibacter indicus LP100 T (Singh et al, 2013a). Two species, 'Pontibacter rhizosphera' IMTB-1969 T (Raichand et al, 2011) and 'Pontibacter salisaro' HMC5104 T (Joung et al, 2011), have been described in publications; however, their names have yet to be validly published.…”
mentioning
confidence: 99%
“…We have already characterized several novel bacterial species from stressed environments including fly ash dumping sites of thermal power plants in Delhi and Kanpur, India (Prakash & Lal, 2006;Prakash et al, 2007), oil-contaminated site, Panipat oil refinery, India (Gupta et al, 2008(Gupta et al, , 2009, and a hexachlorocyclohexane dumpsite, situated at Ummari village, Lucknow, India (Kumar et al, 2008(Kumar et al, , 2015Singh & Lal, 2009;Verma et al, 2009Verma et al, , 2015Sharma et al, 2010;Malhotra et al, 2012;Dwivedi et al, 2013;Singh et al, 2013Singh et al, , 2014Singh et al, , 2015Mahato et al, 2015). To further analyse the bacteria from the hexachlorocyclohexane dumpsite, samples were collected from the drainage system of a lindane-producing unit (Lucknow, Uttar Pradesh, India; 268 549 N 818 099 E).…”
mentioning
confidence: 99%
“…Previous studies from this HCH-contaminated dumpsite site have revealed a predominance of sphingomonads which are potential degraders of HCH (Singh & Lal, 2009;Bala et al, 2010;Garg et al, 2012) along with many species of the genus Pontibacter (Dwivedi et al, 2013;Singh et al, 2013Singh et al, , 2014.…”
mentioning
confidence: 99%